Microfinance poverty assessment tool - Henry, Carla; Consultative Group to Assist the Poorest (Washington, D.C. : World Bank, Consultative Group to Assist the Poor, 2003)
This book provides accurate data on the poverty levels of MFI clients relative to people living in the same community.
At head of title: CGAP.
Includes bibliographical references (p. 205-206).
aug 30/04/13
Loans
Keywords: Microfinance; Poverty